1996
DOI: 10.1243/pime_proc_1996_210_252_02
|View full text |Cite
|
Sign up to set email alerts
|

Aldehydes and Ketones in Engine Exhaust Emissions—a Review

Abstract: Aldehydes and ketones in engine exhaust gases are receiving increased attention and are beginning to be subject to special legislation due to their carcinogenic and ozone formation potential. This paper gives an overview of their properties as well as of the basic chemistry and conditions of their formation in internal combustion engines. Extensive research on the effects of engine operation and fuelling parameters is reviewed with specific references to gasoline, diesel, natural gas and methanol fuelled engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…Regardless of the types of fuel, all internal combustion engines emit considerable amounts of HCHO. Interestingly, usage of alternative fuels can substantially reduce vehicle emissions of nitrogen oxides (NO x ) but may significantly increase emissions of HCHO and other carbonyl compounds (Wagner and Wyszynski, 1996). A recent study by Rappenglück et al (2013) suggests that currently available mobile emission models (e.g., MOBILE6 and MOVES) may significantly underestimate the HCHO emissions from vehicles and there is a non-negligible difference of HCHO emissions between lightduty and heavy-duty diesel vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the types of fuel, all internal combustion engines emit considerable amounts of HCHO. Interestingly, usage of alternative fuels can substantially reduce vehicle emissions of nitrogen oxides (NO x ) but may significantly increase emissions of HCHO and other carbonyl compounds (Wagner and Wyszynski, 1996). A recent study by Rappenglück et al (2013) suggests that currently available mobile emission models (e.g., MOBILE6 and MOVES) may significantly underestimate the HCHO emissions from vehicles and there is a non-negligible difference of HCHO emissions between lightduty and heavy-duty diesel vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…The literature shows that714 the oxidation of aldehydes occurs favorably for temperature higher715 than 850 K[36]. Thus, its formation have tendency of be favorable716 during operation condition that includes lower temperatures.…”
mentioning
confidence: 99%
“…Early work, presumably with older engine and emissions control technology than is commonly used today, suggested that generally some changes to catalyst formulation may be necessary to ensure long-term catalyst durability with methanol (Nichols et al ., 1988 ), but this is not expected to be an issue with present-day technology: fl ex-fuel vehicles have been shown to be capable of meeting limits for formaldehyde when operated on E85 (West et al ., 2007 ) and are expected to be able to do so for other alcohols such as n-butanol (Gingrich et al ., 2009 ). It is known that aldehyde emissions can be successfully neutralized by the type of three-way catalysts typically used to control emissions of modern spark-ignition engines (Menrad et al ., 1988;Wagner and Wyszy ń ski, 1996 ;Shenghua et al ., 2007 ). Gasoline may actually yield greater challenges with respect to aldehydes on legislated drive cycles in the future: Benson et al .…”
Section: Pollutant Emissions Deposits and Lubricant Dilutionmentioning
confidence: 99%